Activity coefficients at infinite dilution of alkanes, alkenes, alkyl benzenes in dimethylphosphate based ionic liquids using gas–liquid chromatography. (December 2015) - Ge, Ming-Lan; Lu, Chun-Yang; Liu, Xiao-Yan; Li, Xiang-Bo; Chen, Jin-Yuan; Xiong, Jie-Ming
Graphical abstract: Highlights: Measurements of activity coefficients at infinite dilution using GLC. 16 organic solutes in the ionic liquids [MMIM][DMP] and [EMIM][DMP]. The excess thermodynamic functions, entropies, and Gibbs energies were calculated. Selectivity and capacity for hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j ) were calculated. Abstract: Activity coefficients at infinite dilution ( γ i ∞ ) for organic solutes: alkanes, alkenes, and alkyl benzenes in two ionic liquids (ILs) 1, 3-dimethylimidazolium dimethylphosphate ([MMIM][DMP]) and 1-ethyl-3-methylimidazolium dimethylphosphate ([EMIM][DMP]) have been measured by the gas–liquid chromatographic method (GLC). The measurements were carried out in the temperature range of (313.15 to 363.15) K. The values of the partial molar excess enthalpies at infinite dilution ( H ‾ i E, ∞ ) were derived from the temperature dependence of the γ i ∞ values. The entropies ( T ref S ‾ i E, ∞ ) and Gibbs energies ( G ‾ i E, ∞ ) of organic solutes at a reference temperature Tref  = 298.15 K were also calculated from the γ i ∞ values. Selectivity ( S ij ∞ ) and capacity ( k j ∞ ) at infinite dilution at T  = 323.15 K have been determined for hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j ). The results were analyzed in comparison to literature data for other ILs with the [MMIM] and [EMIM] cations. For three isomeric xylenes separation problems, selectivity at T  = 323.15 K were also obtained from the γ i ∞ values.